2012
DOI: 10.1007/s10495-012-0792-4
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium kansasii-induced death of murine macrophages involves endoplasmic reticulum stress responses mediated by reactive oxygen species generation or calpain activation

Abstract: Although pathogenic mechanisms of tuberculosis have been extensively studied, little is known about the pathogenic mechanisms of Mycobacterium kansasii. In this work the influence of virulence and ER-stress mediated apoptosis of macrophages during two different strains of M. kansasii infection was investigated. We show that M. kansasii infection is associated with ER stress-mediated apoptosis in the murine macrophage cell line RAW 264.7. Infection of RAW 264.7 cells in vitro with apoptosis-inducing a clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Previously, we suggested that ER stress-mediated apoptosis is important for the regulation of intracellular survival of mycobacteria151821. We noted here that the ER stress response is increased in M1 macrophages after Mtb infection.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Previously, we suggested that ER stress-mediated apoptosis is important for the regulation of intracellular survival of mycobacteria151821. We noted here that the ER stress response is increased in M1 macrophages after Mtb infection.…”
Section: Discussionsupporting
confidence: 59%
“…In our previous reports, we suggested that ER stress-mediated apoptosis plays an important role in the regulation of mycobacterial infection1821. We next determined whether virulent mycobacteria could modulate macrophage polarization to control ER stress.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is well-known that ROS can induce apoptosis and pro-inflammatory cytokine production in macrophages3334. To examine the involvement of ROS generation on the effects of MAV2054 in RAW264.7 cells, the oxidation of 2′,7′-dichlorodihydrofluorescein diacetate (H2DCFDA) was assessed by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…ROS plays a crucial role in the control of mycobacterial growth in macrophages (95,96). Pathogenic mycobacteria suppress free radical production to subvert macrophage control of intracellular bacilli load.…”
Section: Discussionmentioning
confidence: 99%